2017
DOI: 10.1016/j.vaccine.2016.11.064
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant N-terminal domain of spike proteins is a potential vaccine against Middle East respiratory syndrome coronavirus (MERS-CoV) infection

Abstract: The persistent public health threat of infection with the Middle East respiratory syndrome coronavirus (MERS-CoV) highlights the need for an effective MERS-CoV vaccine. Previous studies have focused mainly on the receptor-binding domain (RBD) on the spike protein of MERS-CoV. Herein, we investigated the immunogenicity and protective potential of the recombinant N-terminal domain (rNTD) of spike proteins as a vaccine candidate. BALB/c mice vaccinated with 5 or 10μg of rNTD protein demonstrated a significant hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 56 publications
1
82
0
6
Order By: Relevance
“…As a result, the S protein is also a major target for the development of subunit vaccines against SARS-CoV and MERS-CoV. Both full-length S protein and its antigenic fragments, including S1 subunit, NTD, RBD, and S2 subunit, can serve as important targets for the development of subunit vaccines Mou et al, 2013;Wang et al, 2015;Jiaming et al, 2017;Zhou et al, 2018).…”
Section: Potential Targets For Development Of Sars-cov and Mers-cov Smentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the S protein is also a major target for the development of subunit vaccines against SARS-CoV and MERS-CoV. Both full-length S protein and its antigenic fragments, including S1 subunit, NTD, RBD, and S2 subunit, can serve as important targets for the development of subunit vaccines Mou et al, 2013;Wang et al, 2015;Jiaming et al, 2017;Zhou et al, 2018).…”
Section: Potential Targets For Development Of Sars-cov and Mers-cov Smentioning
confidence: 99%
“…Thus, this fragment can be used as an alternative target for subunit vaccine development. Despite their ability to induce immune responses and/or neutralizing antibodies, NTD and S2 as the targets of subunit vaccines are less immunogenic, eliciting significantly lower antibody titers, cellular immune responses, and/or protection than the other regions, such as full-length, S1, and RBD Jiaming et al, 2017). Therefore, in terms of safety and efficacy, the RBD and/or S1 of S protein could be applied as critical targets for the development of subunit vaccine candidates against SARS-CoV, MERS-CoV, SARSr-CoV, and MERSr-CoV.…”
Section: Potential Targets For Development Of Sars-cov and Mers-cov Smentioning
confidence: 99%
“…that a combination of DNA (S) and recombinant protein (S1) in a heterologous prime-boost immunization strategy induced higher immune response (Nab) compared to each component alone [58]. Additionally, protein-based vaccines were developed in various platforms as virus-like particles (VLPs) [60], nanoparticles [61], peptide-based [62], and subunit vaccines directed against various regions of the spike protein S1 [58], the N-terminal domain [63], and the RBD [48,[64][65][66][67][68][69][70]. Those vaccines have the highest safety profile among vaccine platforms but confer variable degrees of immunogenicity which need adjustment for the dose, adjuvants, and site of administration to get optimal protective responses.…”
Section: Current Mers-cov Vaccine Candidatesmentioning
confidence: 99%
“…55,[61][62][63][64][65] Similarly, for MERS-CoV, the full-length or fragments of S protein, particularly the RBD, has been used to demonstrate partial efficacy in rhesus macaques 66,67 as well as inducing NAbs in small animal models such as rabbits and mice. 59,60,[68][69][70][71][72][73] A recent study showed that residues 377-588 of MERS-CoV S protein RBD were capable of eliciting potent humoral and cellular responses, which could be enhanced by adding MF59 adjuvant. 60,71 As an extra-RBD target, the recombinant N-terminal domain (rNTD) of S protein was used as a vaccine candidate and showed humoral (IgG and NAb) and T cell responses in hDPP4-transduced mice when administered with alum or CpG adjuvant.…”
Section: Protein Subunit Vaccinesmentioning
confidence: 99%
“…60,71 As an extra-RBD target, the recombinant N-terminal domain (rNTD) of S protein was used as a vaccine candidate and showed humoral (IgG and NAb) and T cell responses in hDPP4-transduced mice when administered with alum or CpG adjuvant. 70 MERS-CoV S protein nanoparticles have also been developed as a possible vaccine candidate. Coleman et al 74,75 demonstrated that recombinant MERS-CoV S nanoparticles in combination with Matrix-M1 adjuvant induced NAbs, reduced lung viral titers and MERS-CoV M mRNA to baseline levels in transduced mice, suggesting that MERS-CoV replication was efficiently blocked.…”
Section: Protein Subunit Vaccinesmentioning
confidence: 99%